1999
DOI: 10.1046/j.1439-0418.1999.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and seasonal variability of resistance to insecticides in Cacopsylla pyri L. (Hom., Psyllidae)

Abstract: Pear psylla (Cacopsylla pyri L.) resistance to insecticides was studied in adults using the topical application method. In the Avignon population, the winter forms tested (diapausing generation) showed a greater tolerance to insecticide than the summer forms. High resistance rates, ranging from 25‐ to 180‐fold, were observed for three organo‐phosphorous insecticides. Resistance rates were seven times lower for pyrethrinoids and amitraz and practically nil for carbamates. Inter‐population resistance rates, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 20 publications
6
23
1
3
Order By: Relevance
“…The following results were obtained here on the synergism between deltamethrin and PBO: (i) the rate of synergism between deltamethrin and PBO was more than 10‐fold in all the adult populations (except those from Monêtier: RS = 6.3), in both the summer and the winter forms, (ii) the synergistic effects observed at the larval stage were similar to those observed in the adults, (iii) there was no correlation between the sampling dates and the rates of synergism, (iv) there was no correlation between RR and RS, and (v) deltamethrin was the only one of the three pyrethroïds which was clearly synergized by PBO. The authors of a previous study (B uès et al, 1999) observed no synergism between three organophosphorous (azinphosmethyl, phosmet and monocrotophos) and PBO. When PBO was applied before deltamethrin, the slopes of the regressions were generally smaller than those obtained without PBO.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…The following results were obtained here on the synergism between deltamethrin and PBO: (i) the rate of synergism between deltamethrin and PBO was more than 10‐fold in all the adult populations (except those from Monêtier: RS = 6.3), in both the summer and the winter forms, (ii) the synergistic effects observed at the larval stage were similar to those observed in the adults, (iii) there was no correlation between the sampling dates and the rates of synergism, (iv) there was no correlation between RR and RS, and (v) deltamethrin was the only one of the three pyrethroïds which was clearly synergized by PBO. The authors of a previous study (B uès et al, 1999) observed no synergism between three organophosphorous (azinphosmethyl, phosmet and monocrotophos) and PBO. When PBO was applied before deltamethrin, the slopes of the regressions were generally smaller than those obtained without PBO.…”
Section: Discussionmentioning
confidence: 84%
“…However, this increase was not so sharp during the winter of 1998–1999. These results makes it impossible to state whether the winter form is always more resistant to deltamethrin than the summer form, as has been observed with organophosphates (B uès et al, 1999). Although this orchard did not undergo any specific treatments against psylla or the codling moth during the observation period, there were strong fluctuations in the RR during this period.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations